Exploring CAQDAS - How to Support a Novice User of Computer Aided Qualitative Data Analysis Software - Niedbalski,Jakub (2021)
Abstract: During our classes with students, doctoral students, or while taking part in methodological workshops, we often hear some repeated questions: “Is it worth using the computer-aided qualitative data analysis software and why?” and “Which program should I choose?” Having gathered sizable experience in the field, we can answer these questions by saying that the use of CAQDAS (Computer-Assisted Qualitative Data Analysis Software) makes the process of data analysis more systematic and transparent, and this “forces” to think about data and supports in-depth analysis. The use of CAQDAS requires a certain amount of effort and work due to the need to learn about the environment of a software, but also (or maybe first) to change the perspective, and often some habits concerning how a researcher’s workshop is organized. The choice of appropriate software is highly individual and it requires a thorough consideration from its future user. Therefore, the primary objective we set as the authors of this paper is to present the perspective taken by qualitative researchers who use selected free CAQDAS applications. Our paper is intended mainly for novice CAQDAS users who we would like to advise on how to select appropriate software and familiarize them with the specifics of CAQDAS.